The psychological concept of social sustainability in the workplace from the perspective of sustainable goals: A systematic review - Kobal Grum, Darja; Babnik, Katarina (Frontiers in Psychology, 2022)
Unlike environmental sustainability, social sustainability in the workplace is a relatively new concept that is still searching for its own definition and explanation. Therefore, in this paper, we systematically reviewed and critically evaluated recent research on this topic. In doing so, we identified important constructs that help us better define and understand the phenomenon of social sustainability in the workplace. We focused on articles from 2016 - 2022 with content related to three Sustainable Development Goals (SDGs), namely health and well-being (SDG-3), gender equality (SDG-5), and decent work (SDG-8). Given the harrowing events of the past two years, triggered by the COVID -19 pandemic and the global impact of the war in Ukraine, we also wanted to learn whether other categories, such as security (SDG-11) and peace (SDG-16), are embedded in the concept of social sustainability at work. The articles we studied were found through EBSCOhost, specifically in the Academic Search Complete, Business Source Premier, APA PsycInfo, SocINDEX with Full Text, and GreenFILE databases. We selected 67 articles and organised them according to the four levels of research and practice practice in work and organisational psychology. In reviewing the literature, we identified several constructs that can be classified at four levels of interest in work and organisational psychology. At the level focused on the job/work, we identified two main topics: (i) sustainable job/work characteristics and (ii) sustainable job (re)design. At the people-focused level, we identified the following topics: (i) pro-sustainable self-system, (ii) pro-sustainable job attitudes and motivation, (iii) sustainability work environment perceptions and other mediating mechanisms, and (iv) sustainable job behaviour. The organisation-focused level includes (i) organisations as human systems and (ii) pro-sustainable organisational policies and practices. The last (society-focused) level is defined by two main topics: (i) understanding society as a human system and (ii) pro-social mechanisms. In the discussion, we categorised specific constructs identified within the described focus levels into the theoretical model describing the psychological concept of social sustainability in the workplace from the perspective of sustainable goals.